2013
DOI: 10.3390/v5122931
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Effectiveness of Two RNAi Constructs for Resistance to Pepper golden mosaic virus in Nicotiana benthamiana Plants

Abstract: ToChLPV and PepGMV are Begomoviruses that have adapted to a wide host range and are able to cause major diseases in agronomic crops. We analyzed the efficacy of induced resistance to PepGMV in Nicotiana benthamiana plants with two constructs: one construct with homologous sequences derived from PepGMV, and the other construct with heterologous sequences derived from ToChLPV. Plants protected with the heterologous construct showed an efficacy to decrease the severity of symptoms of 45%, while plants protected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In Nigeria, moderate resistance in four pepper cultivars has been identified [79]. In addition to the conventional breeding, different transgenic approaches for achieving resistance or tolerance have been tested against begomoviruses infecting tomato and pepper [80][81][82] and this may be a way forward for obtaining durable resistance. In West and Central Africa, leaf curl disease is regarded as the most important biotic stress for okra, and there is a lack of viral resistance/tolerance [58,83].…”
Section: Resistancementioning
confidence: 99%
“…In Nigeria, moderate resistance in four pepper cultivars has been identified [79]. In addition to the conventional breeding, different transgenic approaches for achieving resistance or tolerance have been tested against begomoviruses infecting tomato and pepper [80][81][82] and this may be a way forward for obtaining durable resistance. In West and Central Africa, leaf curl disease is regarded as the most important biotic stress for okra, and there is a lack of viral resistance/tolerance [58,83].…”
Section: Resistancementioning
confidence: 99%
“…In chilli, resistance to the Kor strain of cucumber mosaic virus (CMV-Kor, Cucumovirus ) and pepper mild mottle virus (PMMoV; Tobamovirus ) has been developed using sense gene induced posttranscriptional gene silencing (S-PTGS) and co-expression of the coat proteins (CPs) of CMV-Kor and tomato mosaic virus (ToMV; Tobamovirus ) ( Shin et al., 2002 ). siRNA mediated resistance was reported in tobacco against tomato yellow leaf curl virus-Oman (TYLCVOM) ( Ammara et al., 2015 ), pepper golden mosaic virus (PepGMV) ( Medina-Hernández et al., 2013 ), chilli leaf curl virus (ChiLCV), tomato leaf curl New Delhi virus (ToLCNDV), and chilli leaf curl Vellanad virus (ChiLCVeV) ( Sharma et al., 2015 ) and in tomato against tomato yellow leaf curl virus (TYLCV) ( Fuentes et al., 2016 ). CchGLP is a gene that encodes Germin-like proteins (GLPs), which play a crucial role in plant defense against viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotiana benthamiana is an ideal model plant for the investigation of plant–pathogen interaction mainly due to a large number of diverse plant viruses that can successfully infect it, and Agrobacterium -mediated transient gene expression works exceptionally well in N. benthamiana plants ( Norkunas et al, 2018 ). It has been successfully used for the identification of new viral suppressors of RNA silencing and functional analysis of unidentified genes, artificial microRNAs, or RNAi constructs to different plant viruses ( Thomas et al, 2003 ; Peart et al, 2005 ; Goodin et al, 2008 ; Roumi et al, 2012 ; Medinahernández et al, 2013 ). In general, N. benthamiana plants could not be infected by SMV except several reports ( Almeida et al, 2002 ; Gao et al, 2015b ; Jiang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, N. benthamiana plants could not be infected by SMV except several reports ( Almeida et al, 2002 ; Gao et al, 2015b ; Jiang et al, 2017 ). Thereinto, our previous study found that N. benthamiana plants can be systemically infected by an SMV of Watermelon mosaic virus (WMV) chimeric isolate 4278-1 (SWCI-4278-1), which has certain potential to verify the effectiveness of TIR constructs derived from the conserved target fragment (CTF) ( Medinahernández et al, 2013 ). In addition, a recombinant SMV vector, pSMV-GUS was also considered for testing the infectivity of N. benthamiana plants in this study.…”
Section: Introductionmentioning
confidence: 99%